National Savings and Targets for the Federal Budget Balance in the United States. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
The U.S. national savings rate has declined in the 1980s, with both public and private components falling. This paper discusses that decline and whether a policy response is needed. The drop in the private savings rate appears to reflect factors not easily reversible by policy and increases in public saving may thus provide the most effective means of bolstering national savings. Illustrative calculations based on two alternative frameworks indicate that a net national saving rate substantially above its current level could be a desirable objective and that a large federal budget surplus could be needed to that end.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet